Pulmonary artery pressure‐guided therapy in ambulatory patients with symptomatic heart failure: the CardioMEMS European Monitoring Study for Heart Failure (MEMS‐HF). (9th August 2020) - Angermann, Christiane E.; Assmus, Birgit; Anker, Stefan D.; Asselbergs, Folkert W.; Brachmann, Johannes; Brett, Marie‐Elena; Brugts, Jasper J.; Ertl, Georg; Ginn, Greg; Hilker, Lutz; Koehler, Friedrich; Rosenkranz, Stephan; et al.
Abstract : Aims: Heart failure (HF) leads to repeat hospitalisations and reduces the duration and quality of life. Pulmonary artery pressure (PAP)‐guided HF management using the CardioMEMS™ HF system was shown to be safe and reduce HF hospitalisation (HFH) rates in New York Heart Association (NYHA) class III patients. However, these findings have not been replicated in health systems outside the United States. Therefore, the CardioMEMS European Monitoring Study for Heart Failure (MEMS‐HF) evaluated the safety, feasibility, and performance of this device in Germany, The Netherlands, and Ireland. Methods and results: A total of 234 NYHA class III patients (68 ± 11 years, 22% female, ≥1 HFH in the preceding year) from 31 centres were implanted with a CardioMEMS sensor and underwent PAP‐guided HF management. One‐year rates of freedom from device‐ or system‐related complications and from sensor failure (co‐primary outcomes) were 98.3% [95% confidence interval (CI) 95.8–100.0] and 99.6% (95% CI 97.6–100.0), respectively. Survival rate was 86.2%. For the 12 months post‐ vs. pre‐implant, HFHs decreased by 62% (0.60 vs. 1.55 events/patient‐year; hazard ratio 0.38, 95% CI 0.31–0.48; P  < 0.0001). After 12 months, mean PAP decreased by 5.1 ± 7.4 mmHg, Kansas City Cardiomyopathy Questionnaire (KCCQ) overall/clinical summary scores increased from 47.0 ± 24.0/51.2 ± 24.8 to 60.5 ± 24.3/62.4 ± 24.1 ( P  < 0.0001), and the 9‐item Patient Health Questionnaire sum score improved from 8.7 ± 5.9 to 6.3 ± 5.1 ( P  < 0.0001). Conclusion: Haemodynamic‐guided HF management proved feasible and safe in the health systems of Germany, The Netherlands, and Ireland. Physician‐directed treatment modifications based on remotely obtained PAP values were associated with fewer HFH, sustainable PAP decreases, marked KCCQ improvements, and remission of depressive symptoms. Abstract :